Deformation of Ancient Buildings inferred by Terrestrial Laser Scanning methodology: the Cantalovo church case study (Northern Italy)*. - Bonali, E.; Pesci, A.; Casula, G.; Boschi, E. (Archaeometry, 2014)
The study of the health of a building connects humanistic and scientific research, and a complete characterization can be achieved by integrating all the available historical documentation, architectural and metrological studies, as well as laboratory and in situ analyses of the materials. A contactless, non-invasive surveying technique such as terrestrial laser scanning ( TLS) allows the acquisition of dense and accurate geometric and radiometric (electromagnetic measurements such as signal intensity) information about the observed surface of the building, which can be easily integrated with data provided by high-resolution digital imaging. The early Christian Cantalovo church was surveyed for the first time in April 2011, by means of the ILRIS-3D ER very long range scanner. The second and last survey was performed in June 2012, after the main shocks of the Emilia earthquake seismic sequence. A very long range instrument is suitable for fast, simple and independent measurements, due to its technical characteristics and, for this reason, is easily usable for accurate surveying in emergency conditions. The main results are obtained by applying a data analysis strategy based on the creation of TLS-based morphological maps computed as point-to-primitive differences, which allow the creation of a deformation map and its evolution in time.